Fungos de solos da Antártica: prospecção de L-asparaginase e protease e caracterização taxonômica - Vianna, Marina Vitti [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Extreme environments are potential sources for the discovery of new natural products with specific properties for biotechnological applications due to little knowledge about the diversity and genetic resources of microorganisms that inhabit these places. Microorganisms from the Antarctic environment have shown potential for producing active enzymes in mild temperatures with application in various sectors of economic importance. In this context, the present study evaluated the production of proteases and L-asparaginase by filamentous fungi (n= 161) and yeasts (n= 137) isolated from seven different samples of the Antarctic soils (collected in the Antarctic expedition Nov/Dec 2013 - INCT Cryosphere Project). The isolates are being maintained in the research collection linked to the Microbial Resource Center of UNESP (CRM-UNESP). A total of 101 (62.7%) filamentous fungi showed potential for production of L-asparaginase on solid medium (qualitative screening), but in the quantitative screening in liquid medium the enzyme was not produced. Concerning proteases production, 121 (75.1%) filamentous fungi presented halo of degradation on solid medium and 30 (18.6%) isolates showed protease activity above 45.0 U/mL Among them, thirteen (8.7%) isolates were able to produce protease above 100.0 U/mL: seven isolates produced alkaline proteases and six acid proteases. The isolates 5BI (Aspergillus sp.) and 6 MP (Thelebolus sp.) showed the best results in the production of acid and alkaline proteases, respectively, and were submitted to the experimental design. Results indicated a significant increase in protease production at 10 °C and 150 rpm: 7.41 times for the production of acid proteases by the fungus 5BI (1,810.0 U/mL) and 5.38 times (1,542.5 U/mL) for the production of alkaline proteases by the fungus 6MP. For both isolates the conditions applied for the maximum production of proteases were validated. Results related to the assessment of the diversity of the 137 yeasts (MSP-PCR) revealed the presence of 22 different taxa, especially the genera Cryptococcus (21.1%), Rhodotorula e Candida (20.4%). Other less prevalent genera found were: Cystofilobasidium (13.8%), Rhodosporidium (13.1%), Leucosporidium (8.7%), Guehomyces (6.5%), Debaryomyces (3.6%), Bulleromyces (2.9%), and Malassezia (2.1%). Based on the Simpson, Shannon and Chao indexes, the soil BI (biofilm soil, Deception Island) was the most diverse and presented the greatest richness. Analysis of physicochemical parameters of the soils and their diversity revealed that MP (soil under rotten wood, Deception), FE (soil under iron bar, Deception), and GC 4.0 (soil under layer ice, King George) are closed related. The present work presents an overview of the diversity of yeast in different types of soils from Antarctic Islands and reveals the biotechnological potential of filamentous fungi for the production of acid and alkaline proteases.

Ambientes extremos são fontes potenciais para a descoberta de novos produtos naturais com propriedades específicas para aplicação biotecnológica, devido ao pouco conhecimento sobre a diversidade e os recursos genéticos dos micro-organismos que habitam esses locais. Micro-organismos do ambiente Antártico têm demonstrado potencial para produção de enzimas ativas em temperaturas brandas com aplicação em diversos setores de importância econômica. Neste contexto, o presente trabalho avaliou a produção de L-asparaginase e proteases produzidas por fungos filamentosos (n=161) e leveduras (n=137), isolados de oito diferentes amostras de solos da Antártica (coletados na expedição Antártica de nov/dez de 2013 no âmbito do INCT Criosfera). Os fungos filamentosos e as leveduras encontram-se preservados na coleção de pesquisa vinculada à Central de Recursos Microbianos da UNESP (CRM-UNESP). Um total de 101 (62,7%) fungos filamentosos apresentou potencial para produção da enzima L-asparaginase em meio sólido (triagem qualitativa), porém nos testes quantitativos em meio líquido a enzima não foi produzida nas condições utilizadas. Com relação às proteases, 121 (75,1%) fungos apresentaram halo de degradação em meio sólido e 30 (18.6%) isolados apresentaram resultados de atividade de proteases acima de 45,0 U/mL. Dentre eles, 13 (8,7%) foram capazes de produzir proteases acima 100,0 U/mL: sete isolados apresentaram atividade de proteases alcalina e seis de proteases ácidas. Os isolados 5BI (Aspergillus sp.) e 6 MP (Thelebolus sp.) se destacaram na produção de proteases ácidas e alcalinas, respectivamente, e foram submetidos ao planejamento experimental. Os resultados indicaram um aumento significativo na produção de proteases a 10ºC e 150 rpm: 7,41 vezes para a produção de proteases ácidas pelo fungo 5BI (1.810,0 U/mL) e 5,38 vezes (1.542,5 U/mL) para a produção de proteases alcalinas pelo fungo 6MP. Para ambos os isolados as condições aplicadas que resultaram nos valores máximos de produção de proteases foram validadas. Os resultados da avaliação da diversidade das 137 leveduras (MSP-PCR) revelaram a ocorrência de 22 táxons distintos distribuídos em 8 gêneros, com predominância de Cryptococcus (21,1%), Rhodotorula e Candida (20,4%). Outros gêneros menos predominantes encontrados foram: Cystofilobasidium (13,8%), Rhodosporidium (13,1%), Leucosporidium (8,7%), Guehomyces (6,5%), Debaryomyces (3,6%), Bulleromyces (2,9%) e Malassezia (2,1%). Com base nos índices de Simpson, Shannon e Chao o solo BI (solo de biofilme, Deception) foi o mais diverso e o que apresentou a maior riqueza. Análises dos parâmetros físico-quimicos dos solos e de diversidade revelaram proximidade entre os solos MP (solo embaixo de madeira podre, Deception), FE (solo embaixo de barra de ferro, Deception) e CG 4.0 (solo embaixo de camada de gelo, Rei George). O presente trabalho apresenta uma visão geral da diversidade de leveduras nos diferentes tipos de solos de Ilhas Antárticas e revela o potencial biotecnológico de fungos filamentosos para produção de proteases ácidas e alcalinas.
Antarctic soil fungi: prospecting L- asparaginase and protease and taxonomic characterization
Keywords: Antartica; Proteases; L-asparaginase; Diversidade; Microbiologia; Enzimas